Verbal and Non-Verbal Sign in “Elemental” Movie Posters - Wiradinata, I Kadek Adhitya; Utami, Gek Wulan Novi; Dewi, A.A. Sagung Shanti Sari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The title of this study is Verbal and Non-Verbal Signs In “Elemental” Movie Poster. This study is focused on the analysis of verbal and non-verbal signs found in movie posters and the meaning of the signs. There are two aims of this study, they are to identify the verbal and non-verbal signs and explain the meaning of the verbal and non-verbal signs in these movie posters. The data in this study were in the form of images of Elemental movie posters. In this study, there were three movie posters were discussed. Documentation method was used to collect the data. The collected data were analyzed qualitatively based on the theory of semiotic by Saussure, the theory of verbal and non-verbal signs by Dyer, and the theory of color meaning by Cerrato. The result shows that there are two types of signs found in those movie posters namely verbal and non-verbal signs. There are eight verbal signs found in these movie poster, namely “Opposites React”, “Disney”, “PIXAR”, “ELEMENTAL”, “2023”, “Get Fired Up”, “Only In Theater June 16” Those verbal signs give the information to the people about the title of the movie, creator of the movie, and the name of the company, the year of the movie released, the elements of the characters in the movie, the date of the movie released. The nonverbal sign in movie posters consists of appearance, manner, activity, and background.